Is sociality associated with high longevity in North American birds? - Blumstein, D.T (The Royal Society, 2008)
Sociality, as a life-history trait, should be associated with high longevity because complex sociality is characterized by reproductive suppression, delayed breeding, increased care and survival, and some of these traits select for high longevity. We studied the relationship between cooperative parental care (a proxy of complex sociality) and relative maximum lifespan in 257 North American bird species. After controlling for variation in maximum lifespan explained by body mass, sampling effort, latitude, mortality rate, migration distance and age at first reproduction, we found no significant effect of cooperative care on longevity in analyses of species-specific data or phylogenetically independent standardized linear contrasts. Thus, sociality itself is not associated with high longevity. Rather, longevity is correlated with increased body size, survival rate and age of first reproduction.